Strategi Penyelesaian Pembiayaan Bermasalah pada Akad Murabahah di Pt Bank Aceh Syariah Cabang Jeuram - Devi, Santi; Marlina, Lilis (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2024)
This research investigates the strategies for resolving problematic financing in murabahah contracts at PT Bank Aceh Syariah, Jeuram Branch, utilizing a qualitative approach. Primary data was collected through structured interviews and direct observation from February to May 2023. The study's focus includes the main requirements for customers in murabahah contracts, the application of the 5C principle, and methods for resolving problematic financing. The primary informants were the staff of Bank Aceh Syariah, Jeuram Branch, including Mr. Muhammad Junaidi, Mr. Nasrusdi, Mr. Teuku Asnawi, and Mr. Zikran Niam. The results indicate that the murabahah financing process requires comprehensive documentation and financial proof from customers. The application of the 5C principle, particularly focusing on the character of prospective customers, is a crucial step in creditworthiness assessment. Strategies for resolving problematic financing include restructuring stages such as rescheduling and reconditioning, as well as a musyawarah approach with customers. The bank also implements preventive and curative strategies, including comprehensive analysis and evaluation by Account Officers. As a final measure, the sale or auction of collateral is adopted as a resolution solution. In conclusion, the strategies applied by Bank Aceh Syariah, Jeuram Branch, in handling problematic financing demonstrate a comprehensive approach aligned with Sharia principles.